Ecoturismo de base comunitária: diagnóstico para uma construção participativa na barra do Rio Mamanguape-PB - Cruz, Fernanda Tereza Pereira (2015)
Making reference to the practice of tourism in the Barra do Rio Mamanguape community located in the APA of the Barra do Rio Mamanguape - PB and the natural potential of the site for the practice of tourist activities, the purpose of this study sought to conduct a diagnosis of tourist community, analyzing their interrelationships to the participatory construction of Ecotourism Community Base. Analyze the dynamic tourism and its potential for tourism development is preliminary to the planning of tourism in a region action, especially for the tourism develops in a responsible manner while minimizing impacts to the environment and culture of indigenous communities. For purposes of analysis, literature searches were conducted primarily about the concepts that concern research. Shortly after empirical research with qualitative and quantitative basis were conducted from January 2014 to October 2014 in Barra do Rio Mamanguape community, with the help of tools like questionnaires and interviews with internal and external stakeholders of the local tourism development. Although surveys were conducted onsite for identification of in loco tourism and documentary research in order to recognize the tourist flows in the region. From the data analysis it was found the potential for participatory community building community-based ecotourism as regards the tourism potential, but for the development of fact, there is still much to be articulated not only by the interest of the community site, but the support from government to subsidize its construction. Although there is potential for its development, it is necessary a sharper insight into their future development, since the current impasse occurs from the sanction of the management plan for the conservation unit community is located, because through this rules for the use of territories which could draw the attention of private sector large for construction of tourism in the region, which would extinguish the time of the community in developing tourism in the region as a community will be dictated. However, protrudes through this research the importance of articulating the community, with government and non-government planning of participatory tourism agencies, preceding the establishment of the private tourism sector in the region.